2016
DOI: 10.1002/ange.201604554
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐Doped Antiperovskite Electrolyte for All‐Solid‐State Lithium‐Ion Batteries

Abstract: Af luorine-doped antiperovskite Li-ion conductor Li 2 (OH)X (X = Cl, Br) is shown to be ap romising candidate for as olid electrolyte in an all-solid-state Li-ion rechargeable battery.S ubstitution of F À for OH À transforms orthorhombic Li 2 OHCl to ar oom-temperature cubic phase,w hichs hows electrochemical stability to 9Vversus Li + /Li and two orders of magnitude higher Li-ion conductivity than that of orthorhombic Li 2 OHCl. An all-solid-state Li/LiFePO 4 with F-doped Li 2 OHCl as the solid electrolyte sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 34 publications
0
73
0
3
Order By: Relevance
“…[25] Heating from RT to 40 °C leads to noticeable changes in the crystal lattice ( Figure 2C). Mistakenly previously treated as orthorhombic to cubic transition, [11,13,19] we have shown that at 40 °C contaminant-free Li 2 OHCl exists in the tetragonal phase with lattice parameters a = 3.91 Å, b = 3.91 Å, c = 3.92 Å ( Figure 2C). Mistakenly previously treated as orthorhombic to cubic transition, [11,13,19] we have shown that at 40 °C contaminant-free Li 2 OHCl exists in the tetragonal phase with lattice parameters a = 3.91 Å, b = 3.91 Å, c = 3.92 Å ( Figure 2C).…”
Section: Structural Characterizationsmentioning
confidence: 58%
See 4 more Smart Citations
“…[25] Heating from RT to 40 °C leads to noticeable changes in the crystal lattice ( Figure 2C). Mistakenly previously treated as orthorhombic to cubic transition, [11,13,19] we have shown that at 40 °C contaminant-free Li 2 OHCl exists in the tetragonal phase with lattice parameters a = 3.91 Å, b = 3.91 Å, c = 3.92 Å ( Figure 2C). Mistakenly previously treated as orthorhombic to cubic transition, [11,13,19] we have shown that at 40 °C contaminant-free Li 2 OHCl exists in the tetragonal phase with lattice parameters a = 3.91 Å, b = 3.91 Å, c = 3.92 Å ( Figure 2C).…”
Section: Structural Characterizationsmentioning
confidence: 58%
“…Conductivities of the uncontrollably doped Li 2 OHX can thus be significantly altered, since only 0.005 at% of dopants may be sufficient to drastically change the conductivity values. [11] Finally, uncontrolled moisture in the synthesis of these materials or leaks in the electrochemical cells were found (by our team and by another group [15,18] ) to significantly change the measured conductivities and may potentially be responsible for some of the previously reported conductivity values. Unfortunately, such a control is often ignored.…”
mentioning
confidence: 78%
See 3 more Smart Citations